DAYA SAING DAN STRATEGI PENGEMBANGAN MINYAK SAWIT DI INDONESIA - Jauhar Samudera Nayantakaningtyas; Heny K. Daryanto (Jurnal Manajemen & Agribisnis, 2012)
ABSTRACTThe aims of this study were to analyze the competitiveness of Indonesian Crude palm oil CPO products in the international market and to analyze the strategy to improve the competitiveness of Indonesian CPO. The analysis methods used this research were descriptive qualitative methods. The tools used to analyze the competitiveness of palm oil is Revealed Comparative Advantages and Porter Diamond Theory, while the development of the strategy used to determine the SWOT method. Based on the analysis of Porter's Diamond System and revealed comparative advantages, this study concluded that the competitiveness of Indonesian CPO was pretty strong, but it still needed a strategy to strengthen its competitiveness especially on derivative products. Some of the routine strategies that need to be done every year, are the development of the CPO industry human resources through training and innovation activities, paying attention to national and international issues by improving government policies, downstream industrial development and palm oil value-added increase, enhance cooperation with manufacturers from other countries through promotions.Keywords: crude palm oil, competitiveness, strategy, analysis of porter's diamondABSTRAKTujuan penelitian ini adalah menganalisis daya saing produk Crude Palm Oil (CPO) Indonesia di pasar internasional dan menganalisis strategi peningkatan daya saing CPO Indonesia. Metode pengolahan dan analisis data yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Alat  yang digunakan untuk menganalisis daya saing minyak sawit  adalah Revealed Comparative Advantages dan Teori Berlian Porter, sedangkan untuk mengetahui strategi pengembangan digunakan metode SWOT. Hasil analisis Sistem Berlian Porter dan revealed comparative advantages disimpulkan bahwa daya saing CPO Indonesia cukup kuat, namun masih diperlukan adanya strategi untuk memperkuat terutama pada produk turunan CPO. Strategi rutin yang harus dilakukan setiap tahunnya antara lain pengembangan sumber daya manusia pelaku industri minyak sawit dengan pelatihan dan kegiatan inovasi, memperhatikan isu nasional dan internasional dengan memperbaiki kebijakan pemerintah, pengembangan industri hilir serta peningkatan nilai tambah minyak sawit, dan meningkatkan pola kerja sama dengan produsen negara lain melalui promosi.Kata kunci: minyak sawit, daya saing, strategi, analisis porter's diamond